PENGARUH SKEMATA STRUKTUR BAHASA INDONESIA TERHADAP KECAMPINGAN KALIMAT (ILL-FORMEDNESS) BAHASA INGGRIS PADA MAHASISWA JURUSAN PENDIDIKAN BAHASA INGGRIS IKIP PGRI SEMARANG: Sebuah Kajian Morfosintaksis - Nur Hidayat; Rahmawati Sukmaningrum; Siti Musarokah (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2011)
The morfosyntactical errors in students?óÔé¼Ôäó writing composition have been a phenomenon that both writing teachers and other faculty members have complained about. Those errors are not only made by junior students, but also made by senoir students at the university level. One of the reasons of making those morfosyntactical errors is that our students still use their background knowledge of Indonesian sentences?óÔé¼Ôäó structure in their English writing.?é?á?é?á The main objective of this research is to investigate the influence of schemata of Indonesian language structure toward the ill-formedness of English sentences. In brief, this research studies the morfosyntax elements that can cause the formation of ill-formed sentences, the types of ill-formed sentences made by Indonesian students in writing English composition, and also to investigate the students?óÔé¼Ôäó difficuties in writing English. The data of this research was taken from the 3rd semester students of the English Education Department of IKIP PGRI Semarang. The researchers collected the data by (1) Observation and mid semester test result to choose the students. Those who got the score 75 or upper were choosen as the repondents. (2) Questionnaire, and (3) The writing test. From the findings, it was found that the schemata of Indonesian language structure give a significant influence toward the ill-formedness of students?óÔé¼Ôäó English sentences. The most frequent types of ill-formedness are from: noun form and tenses. This fact indicates that our students have difficulty mostly in those two types of topic. Key Words: Morfosyntax, Schemata, Ill-formed Sentences